Reducing Misuse of Data in Motion through Surveillance of Logs. - William, Ahamya; Mirembe, Drake; Nabaasa, Evarist (nternational Journal of Technology and Management, 2023)
This paper explores the reducing misuse of data in motion through surveillance of logs in Uganda. Using a descriptive cross-sectional research design, this study sampled 184 participants comprised of car trackers experts and owners/ drivers of cars with tracking systems and collected data using structured questionnaires. Various analyses and tests including correlation and regression were conducted. The findings revealed that H1a, H1b and H1C are accepted with respect to surveillance of logs and reducing misuse of data in motion. Conversely, surveillance of log techniques was observed to explains around 64.4% of the variations, leaving the remaining 35.4% be explained by others, e.g., internet tracking, cellphone triangulation, satellite tracking etc. However, a critical look at the explanatory potential of each variable (the standardized Beta co-efficient), revealed that surveillance of logs techniques predicts reducing misuse of data in motion negatively. The researcher recommends undertaking mediation and interaction effects amongst variables and well as establishing the longitudinal results of the relationship between study variables.
Keywords: Data in motion; Descriptive cross-sectional research design; Cellphone triangulation; Satellite tracking; Standardized Beta coefficient